Aspectos da biologia, variabilidade genética e estrutura sociogenética dos agregados de Digelasinus diversipes (Kirby, 1882) (Hymenoptera: Agridae) - Boraschi, Daniele (Universidade Federal de São Carlos, 2003)
Symphyta is a suborder of Hymenoptera, which presents primitive characters, like absence of constriction at the base of the abdomen. Symphyta larvae are phytophagous and feed gregariously, causing damage to agricultural crops, ornamental plants and forests stands, especially in temperate zones. In this group researches focus mainly on ecological aspects related to pests control. There are few data about population genetic structure, and studies about genetic variability exhibit disagreeable data. This study attempts to elucidate some aspects of the biology of Digelasinus diversipes, a Neotropical Symphyta with active larvae from November until March which host in Eugenia glazioviana (Myrtacea) trees, where cocoon masses can be found. Genetic variability and population structure were measured by allozymic analyses through starch gel electrophoresis. Cocoon masses were collected in 2000 and 2001, in two areas of the Estação Ecológica Jataí (Luiz Antônio, SP 21º25 S, 47º50 W). Field observations evidenced i) Digelasinus diversipes larvae disperse during foraging, among neighboring trees; ii) larvae from different ovipositions associate to cocoon mass communal construction, observation corroborated by the low relatedness coefficient among individuals of cocoon mass; iii) adults are shortlived; males are smaller than females, which emerge with all eggs matured for fecundation and/or oviposition; iv) the secondary sex ratio, measured by individuals emerged at laboratory, are female-biased. Electrophoretic analyses reveal high levels of average heterozigosity (Hobs = 0.094±0.025SE) for this species, contrasting with previous data for other Hymenopteran species. There were no significant levels of inbreeding inside samples, but the population was structured, suggesting low levels of gene flow, a consequence of their low dispersal ability.
Keywords: Genética de populações; Aspectos biológicos; Symphyta; CIENCIAS BIOLOGICAS::GENETICA